Circular Economy as a Strategic Option for Achieving Sustainable Development in Iraq for the Period 2013–2024 - Abdalkadhem Jabbar , Eman (Iraqi Journal for Administrative Sciences, 2026)
This research explores the circular economy as a strategic approach for sustainable development in Iraq, focusing on the environmental, economic, and social challenges the country faces. It examines the link between the circular economy and the 2030 Sustainable Development Goals (SDGs), offering practical recommendations for its implementation. The study used both quantitative and qualitative analyses, gathering data from sources like the World Bank, UNIDO, and Iraq’s Ministry of Environment. The elbow method categorized the data into economic groups, while K-Means cluster analysis identified key factors influencing the circular economy's success. The findings show that the circular economy could significantly boost resource sustainability and reduce waste in Iraq. However, challenges such as dependence on oil, pollution, and high poverty remain. The study also highlights the need for more private sector investment and efforts towards carbon neutrality to achieve sustainable growth. Specialized strategies for each economic group are essential for success.